Assessing the Vulnerability of Mangrove Habitats in the Coastal Area of Biak Timur District, Papua, Indonesia - Nifaan, Welmincie Milana; Pattiasina, Thomas Frans; Purba, Gandi Yantri Sevantina; Toha, Abdul Hamid A.; Manuhutu, Jafry Ferdinan; Boli, Paulus; Pattiasina, Selfinus (Biotropika: Journal of Tropical Biology, 2025)
The vulnerability of mangrove habitats to environmental changes driven by anthropogenic activities and climate change is a critical concern for sustainable ecosystem management. This study assesses the vulnerability of mangrove habitats along the coastal area of Biak Timur District, Papua, using the Coastal Vulnerability Index (CVI) method. The CVI integrates five key variables: coastline profile, duration of tidal inundation, maximum tidal inundation height, salinity, and substrate type. Coastline profile data were derived from a decadal analysis (2013–2023) of shoreline changes. Tidal inundation duration and height were obtained through tidal data analysis, while salinity and substrate data were collected through field surveys and laboratory analyses. Each variable was scored and weighted within the CVI framework. The results indicate that the mangrove habitat in Biak Timur is in the "high vulnerability" category, with a CVI score of 5.69. This suggests a significant susceptibility to degradation from environmental changes, particularly those caused by human activities and climate change. Effective management should focus on minimising anthropogenic impacts and promoting sustainable use of mangrove resources.